2008
DOI: 10.1248/bpb.31.400
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Tumor Metastasis by Liposomal .BETA.-Sitosterol Intake

Abstract: To investigate chemopreventive effect of liposomal b b-sitosterol on tumor metastasis, we prepared liposomal b b-sitosterol composed of egg yolk phosphatidylcholine for oral delivery. Although orally administered b b-sitosterol (4 m mmol as b b-sitosterol/mouse) was not absorbed into plasma, the amount of immune response cytokines such as IL-12 and IL-18 was increased in the small intestine after the liposome intake. Moreover, after daily oral administration of the liposome for 7 d, natural killer (NK) cell ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 32 publications
(28 reference statements)
3
37
0
Order By: Relevance
“…SIT has been reported to elicit a multitude of bioactivities, which include, antioxidant [40], anticancer [5], antiinflammatory [6], angiogenic [11,28], chemopreventive [16], and immunomodulatory activities [8][9][10]. SIT is indicated for hypercholesterolemia [24] coronary heart disease [38], and benign prostate hyperplasia [39].…”
Section: Introductionmentioning
confidence: 99%
“…SIT has been reported to elicit a multitude of bioactivities, which include, antioxidant [40], anticancer [5], antiinflammatory [6], angiogenic [11,28], chemopreventive [16], and immunomodulatory activities [8][9][10]. SIT is indicated for hypercholesterolemia [24] coronary heart disease [38], and benign prostate hyperplasia [39].…”
Section: Introductionmentioning
confidence: 99%
“…BS has poor absorptivity and therefore additives for enhancing its bioavailability or drug delivery with different dosage forms did not progress extensively even though its pharmacokinetic and bioavailability data was reported long ago [72,73,80]. Liposomal BS has been reported along with its ability to increase natural killer cell activity and decrease metastatic colonies in the lungs significantly in comparison to the control group [198]. BS has been reported to act as a model drug or substance for a novel formulation [199] and to test the efficacy in emulsion form [200].…”
Section: Drug Delivery With Beta-sitosterolmentioning
confidence: 99%
“…Numerous experimental studies have demonstrated the antiproliferative effects of ␤-sitosterol and stigmasterol on colon, breast, prostate, stomach and lung cancers (Choon et al, 2009;Rubis et al, 2008;Younghuan et al, 2009). Also, has been studied the effect of reduction of metastasis presented by these compounds (Imanaka et al, 2008). The mechanisms of action by which is achieved the antitumor activity have also been elucidated, these substances can alter the membranes of tumor cells, can activate the sphingomyelin cycle, activate caspases, suppress the expression of bcl-2 and increase bax gene expression (Awad and Fink, 2000).…”
Section: Chemical Analysis Of the Hexane Fraction Of Methanolic Extramentioning
confidence: 99%